Topographic Characterization of Disposable Carbon Pencil Modified Electrodes - Berbejillo, J. (2004)
Carbón pencil electrodes are proposed as supporting material for the fabrication of disposable devices through surface modification by bismuth plating and polyaniline formation. The surface characteristics were assessed by fractal analysis under semi- infinite linear diffusion employing a soluble molecular probe, and scanning electrón microscopic analysis. The results indicate that the surface topography for bismuth- modified electrodes corresponds to a 2-dimensional smooth surface, while for polyaniline-modified electrodes, a surface fractal dimensión of 2.76 was obtained. These topographic characteristics indicate that bismuth-modified carbón electrodes are suitable for anodic stripping analysis, and polyaniline ones, due to the surface irregularities, may result a good supporting material for biomolecules attachment.